Manajemen Praktikum Bahasa Arab Mahasiswa Prodi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan UIN Mataram - Fathul Maujud (PALAPA, 2022)
One of the problem in education that is getting attention by government's is the problem of improving the quality of education. The improvement programs of education quality can be achieved when the process of teaching and learning can take place properly, efficiently and effectively, and supported by practicum programs as a medium to strengthen and apply the skills which have possessed by students. To guiding the students of Arabic language and as a part of the efforts to improve the quality of academic services and the quality of graduates in higher education, it is very important to build strategically to develop practicum programs by study programs and lecturers. The research approach is using qualitative research with descriptive method with data collection techniques are observation, interviews and documentation. Meanwhile, the data analysis uses an interactive data analysis pattern using the Miles and Hubermans model. The result is the implementation of practicum program management is carried out in some stages; the preparation of the practicum program, the implementation, the evaluation of the practicum and the management of the practicum which have implications for development of Arabic language especially for students of the Arabic Language Education Program.